A highly efficient activated carbon by chemical activation method for adsorption of paraquat (toxin) - Rahman, Md. Mokhlesur (2012)
The ambient condition for preparing the highly efficient activated carbon has been investigated in this work. The effects of different activation temperatures on the pore structure and surface morphology of highly efficient activated carbon (AC) derived from waste palm shell by chemical activation method using phosphoric acid as activating agent were studied. For activation, different activation temperatures in the range of 5500C-6500C were carried out. Activated carbon with well developed pore size were produced at activation temperature of 6000C for 2 hours. At this temperature the Brunauer , Emmett and Teller (BET) surface areas are 1280 m2g-1, the total pore volume for adsorption and desorption are 0.871767cm3 g-1. Scanning Electron Microscope also confirmed the porosity of the highly efficient activated carbon. Finally it was tested in vitro to determine its adsorbing capacity for paraquat as a toxin. For optimum adsorption ability of activated carbon for paraquat, 0.9% NaCl solution is the most suitable solvent. The paraquat preferentially adsorbed onto the activated carbon in NaCl solution. The adsorption ability of the activated carbon (the amount adsorbed) for paraquat observed to be 99.9 mg g-1.